SCOTISM, THOMISM AND IT RECEPTION IN GIZEL’S PHILOSOPHY - Угляр, Я. Ю. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article is devoted to general aspects of Gizel’s studies and basic philosophical views of Western European representatives like Duns Scotus and Thomas Aquinas. A philosophical dialogue between the representatives of Western philosophy and Gizel gives us an idea of the philosophical reception that prevailed and influenced the most the philosophy of the scientist.